The Impact of the HPP Law on Changes in MSME Income Tax Rates and Modernization of the Tax System on MSME Taxpayer Compliance - Hutagaol, Layon (IJBLE Scientific Publications Community Inc., 2025)
The Law on Harmonization of Tax Regulations (UU HPP) has brought significant changes to the taxation system in Indonesia, especially regarding income tax rates for Micro, Small, and Medium Enterprises (MSMEs). This study aims to analyse the influence of the Law on HPP and the modernization of the tax system on MSME taxpayer compliance. The research method uses a quantitative approach with data collection through a survey of MSME actors in various sectors. The results of the study show that the reduction in income tax rates on MSMEs increases the level of taxpayer compliance. In addition, the application of technology in the taxation system facilitates tax reporting and payment, which in turn encourages MSME involvement in fulfilling their tax obligations. Tax modernization contributes to transparency and efficiency, so that MSMEs feel more comfortable in carrying out their tax obligations. The results of this study are expected to provide input for policy makers in formulating more effective strategies to improve tax compliance and encourage the growth of the MSME sector in Indonesia